Concomitant food intake does not affect the efficacy of entecavir in chronic hepatitis B patients with virological response: a randomized, multicenter, noninferiority trial - Cho EJ; Yu SJ; Kwon SY; Kim JH; Kim DY; Kim W; Lee JS; Lee JW; Lee YJ; Chae HB; Yoon JH (Dove Medical Press, 2018)
Eun Ju Cho,1 Su Jong Yu,1 So Young Kwon,2 Ji-Hoon Kim,3 Do Young Kim,4 Won Kim,5 June Sung Lee,6 Jin Woo Lee,7 Youn Jae Lee,8 Hee Bok Chae,9 Jung-Hwan Yoon1 1Department of Internal Medicine, Liver Research Institute, Seoul National University College of Medicine, Seoul, South Korea; 2Department of Internal Medicine, Konkuk University School of Medicine, KonKuk University Hospital, Seoul, South Korea; 3Department of Internal Medicine, Korea University Guro Hospital, Korea University College of Medicine, Seoul, South Korea; 4Department of Internal Medicine, Yonsei University College of Medicine, Seoul, South Korea; 5Department of Internal Medicine, Seoul Metropolitan Government Seoul National University Boramae Medical Center, Seoul, South Korea; 6Department of Internal Medicine, Ilsan Paik Hospital, Inje University College of Medicine, Goyang, South Korea; 7Department of Internal Medicine, Inha University School of Medicine, Incheon, Korea; 8Department of Gastroenterology, Inje University Busan Paik Hospital, Busan, South Korea; 9Department of Internal Medicine, Chungbuk National University Hospital, Chungbuk National University College of Medicine, Cheongju, South Korea Background: Little clinical data are available about the effect of food on the antiviral efficacy of entecavir for chronic hepatitis B virus (HBV) infection. The present study evaluated whether entecavir administration in the fed state had comparable efficacy to the fasted condition for maintenance of viral suppression in HBV-infected patients with virological response on entecavir therapy.Methods: In this multicenter, randomized, open-label, noninferiority study, patients who were currently receiving entecavir and showed a serum HBV DNA level of <20 IU/mL were randomized to take entecavir either under the fasted or fed condition for 48 weeks.Results: We randomly assigned 50 patients to the fasted group and 46 patients to the fed group. The full analysis set consisted of 49 patients in the fasted group and 44 patients in the fed group. At week 48, the proportion of patients with HBV DNA <20 IU/mL was not significantly different between the fasted and fed groups (98% vs 100%, P=1.00). The mean log10 HBV DNA changes from baseline were similar between the two groups (-0.004 vs -0.012 log10 IU/mL, P=0.43). There were no significant differences in the proportions of patients with normal alanine aminotransferase (87.8% vs 95.5%, P=0.27) and hepatitis B e-antigen seroconversion (0% vs 6.7%, P=0.47) between the two groups. None of the patients showed viral breakthrough. In pharmacokinetic analysis, the maximum concentration and the area under the concentration–time curve to the last quantifiable concentration decreased by 26.4% and 9.3%, respectively, in the fed group compared with the fasted group. However, the differences between two groups were not statistically significant (P=0.28 and 0.83, respectively).Conclusion: In patients with virological response under entecavir therapy, concomitant food intake did not affect the antiviral efficacy. For patients with adherence problem, taking entecavir with food may be considered to improve compliance. Keywords: chronic hepatitis B, entecavir, food effect, efficacy